The influence of nitrogen admixture on concentration of an electronic–excited helium atoms in atmospheric pressure glow discharge - Arkhipenko, V.I.; Kirillov, A.A.; Simonchik, L.V.; Zgirouski, S.M. (Вопросы атомной науки и техники, 2005)
The concentrations of the low-excited helium atoms in states 2¹S, 2¹P, 2³S and 2³P were determined in the atmospheric pressure glow discharge in helium (99.98%He) and in helium with a nitrogen admixture (99.5%He + 0.5%N2). It was shown that the adding of nitrogen into helium leads to the drastically reduction of concentration of both the low-excited helium atoms and ions. Визначено концентрації низьких збуджених атомів гелію в станах 2¹S, 2¹P, 2³S і 2³P у тліючому розряді при атмосферному тиску в гелії (99.98%He) і в суміші гелію з азотом (99.5%He + 0.5%N2). Показано, що додавання азоту в гелій приводить до істотного зменшення як заселенностей нижніх збуджених рівнів гелію, так і концентрації іонів гелію. Определены концентрации низких возбужденных атомов гелия в состояниях 2¹S, 2¹P, 2³S и 2³P в тлеющем разряде при атмосферном давлении в гелии (99.98%He) и в смеси гелия с азотом (99.5%He + 0.5%N2). Показано, что добавление азота в гелий приводит к существенному уменьшению как заселенностей нижних возбужденных уровней гелия, так и концентрации ионов гелия.